2023
DOI: 10.1002/adhm.202300821
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ions Functionalized Metal–Organic‐Framework Nanozyme for Tumor Microenvironment Regulating and Enhanced Photodynamic Therapy for Hypoxic Tumor

Abstract: Photodynamic therapy (PDT), as a light irradiation inducing reactive oxygen species (ROS) generation for cancer treatment, offers facile and promising solutions with respect to spatiotemporal control of ROS generation, and minimizes the systemic toxicity and side effects for highly precise tumor therapy. However, the PDT efficiency is often severely compromised by the complex tumor microenvironment (TME), such as the hypoxic condition and overexpressed antioxidants. Here, for the first time, a bimetallic ion–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…PDT involves the utilization of photosensitizer-converted light energy to generate cytotoxic 1 O 2 upon exposure to light irradiation. However, the efficacy of PDT alone is often compromised by the hypoxic tumor environment. Consequently, nanozymes with CAT-like activity offer a solution to this predicament by converting high concentrations of H 2 O 2 in the tumor area into O 2 , thereby reinforcing PDT. , For example, Liu et al developed a precisely defined and homogeneous nanoplatform (Ce6/Ftn@MnO 2 ) comprising MnO 2 as a CAT-like nanozyme, chlorin e6 (Ce6) as a photosensitizer, and ferritin (Ftn) as an inherent tumor-targeting nanovector for enhanced PDT of tumors (Figure A) . The in vitro experiment demonstrated that groups II (Ce6/Ftn@MnO 2 + H 2 O 2 , pH 7.4) and III (Ce6/Ftn@MnO 2 + H 2 O 2 , pH 6.0) exhibited a higher concentration of dissolved O 2 compared to group I (H 2 O 2 ), thereby confirming superior CAT-like performance of the Ce6/Ftn@MnO 2 (Figure B).…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…PDT involves the utilization of photosensitizer-converted light energy to generate cytotoxic 1 O 2 upon exposure to light irradiation. However, the efficacy of PDT alone is often compromised by the hypoxic tumor environment. Consequently, nanozymes with CAT-like activity offer a solution to this predicament by converting high concentrations of H 2 O 2 in the tumor area into O 2 , thereby reinforcing PDT. , For example, Liu et al developed a precisely defined and homogeneous nanoplatform (Ce6/Ftn@MnO 2 ) comprising MnO 2 as a CAT-like nanozyme, chlorin e6 (Ce6) as a photosensitizer, and ferritin (Ftn) as an inherent tumor-targeting nanovector for enhanced PDT of tumors (Figure A) . The in vitro experiment demonstrated that groups II (Ce6/Ftn@MnO 2 + H 2 O 2 , pH 7.4) and III (Ce6/Ftn@MnO 2 + H 2 O 2 , pH 6.0) exhibited a higher concentration of dissolved O 2 compared to group I (H 2 O 2 ), thereby confirming superior CAT-like performance of the Ce6/Ftn@MnO 2 (Figure B).…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…This involves analyzing interactions at the molecular level using techniques such as Raman spectroscopy to detect changes in cell membrane composition and structure. Concurrently, conducting relevant in vivo and in vitro experiments is critical for assessing toxicity and biocompatibility. To this end, ongoing research into the complex mechanisms of SAzymes toxicity is necessary to ensure their responsible utilization in biomedical fields.…”
Section: The Impact Of Sazymes On Biological Systemsmentioning
confidence: 99%
“…Many kinds of inorganic nanomaterials can be intracellularly synthesized through bioreduction, detoxification, or biomineralization. [21] Because of their unique physicochemical properties, they have shown distinguished performance in different types of cancer treatment including but not limited to photothermal therapy (PTT), [22,23] chemodynamic therapy (CDT), [24,25] enhanced radiotherapy (RT), [26,27] etc. Usually, such therapeutic modalities can elicit immunogenic cell death (ICD) via inducing dying tumor cells to release damage-associated molecular patterns (DAMPs), which have potential to promote dendritic cells (DCs) maturation for enhanced antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%